Avaliação de inibidores de incrustação em operações de produção de petróleo - Lima, Adriano Max de Camurça (2020)
A variation in temperature and pressure during oil production sets an adequate scenario for the appearance of inorganic deposits. Caused by changes in these parameters and by minerals dissolved in water with petroleum, a mineral causes numerous problems in industrial sectors. The application of inhibitors is necessary to delay or prevent inorganic deposition in machines and equipment involved in the production processes. In this work, the inhibition efficiency of six commercial products based on phosphonate used to prevent the deposition of CaCO3 was evaluated. Phosphonic diethylene triaminopentamethylene acid (DETPMP) and the commonly used amino trismethylene phosphonic acid (ATMP), and new chemicals, petrolab A (PLBA), petrolab B (PLBB), petrolab C (PLBC) and petrolab D (PLBD). The tests were performed varied as temperatures and doses of application of the inhibitors. Measures to determine the concentration of calcium cations were made using atomic absorption spectrophotometry. A scanning electron microscopy (SEM) was performed to investigate morphological changes in the crystals, following the solutions in which the inhibitors detected the best results. The results shown in the ATMP showed better results at a temperature of 60ºC and the inhibitors PLBC and PLBD showed better results in the tests performed at 80ºC and 100ºC, respectively. The crystals obtained from experiments described morphological deformations, with each inhibitor acting differently on the crystalline surfaces. The dynamic efficiency test revealed that the behavior of the selected inhibitor is directly activated in the conditions and in the configuration of the product application scenario, the PLBD inhibitor exhibits different performances in the synthetic scenario and in the real scenario.